Teaching Electrical Engineering Terms Using Pictures - Fibri Indira Lisanty AD; Sri Rahayu (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2023)
This thesis is aimed at finding out: (1) whether the application of pictures is effective or not to build students’ vocabulary at Electrical Department of SMKN 2 Palopo. (2) the students’ response towards the application of pictures to build students’ vocabulary at Electrical Department of SMKN 2 Palopo. This research used pre-experimental method where the treatment was conducted in six meetings. Furthermore, the population of this research was the eleventh year students of SMKN 2 Palopo in academic year 2022-2023. There was only one class with 28 students. In determining the sample of this research,the researcher used total sampling technique. The researcher took all students as sample and the number of sample was 28 students. The finding of this research shows that the application of pictures is effective in building the eleventh grade students’ vocabulary of SMKN 2 Palopo. It was proven by the fact that there was a significant difference between the students’ mean score of the pretest and the posttest. In the pretest, the students’ mean score is 70.71 and the students’ mean score in posttest is 93.14. Moreover, it also could be seen by comparing the result of t-test and t-table where t-test is higher than t-table (9.67>2.093). It means that the hypothesis is received (tt> t0). Then, the eleventh grade students of SMKN 2 Palopo have positive response on the application of pictures in building students’ vocabulary.It was proven by looking their responses to the statements of the questionnaire. In questionnaire, the statement no 2 and 7 are related to pictures as a strategy can create an exciting learning process.